Correlation between Lumenal Geometry Changes and Hemodynamics in Fusiform Intracranial Aneurysms - Jou, Liang-Der (AJNR Am J Neuroradiol, 2005)
BACKGROUND AND PURPOSE: Hemodynamics may predispose aneurysms to rupture; however, hemodynamic descriptors that can describe aneurysm growth are not well understood. We examined the relationship between hemodynamics and growth of 2 fusiform basilar artery aneurysms in an effort to define hemodynamic variables that may be helpful in predicting aneurysmal growth. METHODS: Two patients with basilar fusiform aneurysms of a similar size were followed for a 2-year period. The lumenal geometry and inflow and outflow rates were acquired by using MR angiography and velocimetry, respectively. The location of aneurysmal growth was identified by coregistering aneurysm models that were acquired at different times. Hemodynamic descriptors were calculated by using computational fluid dynamic simulations and compared with aneurysm growth pattern. RESULTS: One patient had an aneurysm that grew significantly, but a similar-sized aneurysm in the other patient remained unchanged. The largest aneurysmal growth (∼3 mm/year) was found at the inferior side (lower part) of the aneurysm, where the wall shear stress was very low (<0.1N/m(2)). The general flow patterns did not change with time, even in the aneurysm that grew, but histograms of wall shear stress were very different in these 2 patients. CONCLUSIONS: This study investigates whether hemodynamic descriptors can be correlated with regional changes in aneurysm lumen morphology on a patient-specific basis. That capability will permit the testing, in longitudinal studies, of hypotheses as to which mechanisms are the most important in aneurysm growth.